HIV-related stigma and discrimination among health care workers during early program decentralization in rural district Gunungkidul, Indonesia: a cross-sectional study - Gaby G. Langi; Arie Rahadi; Ignatius Praptoraharjo; Riris A. Ahmad (BMC, 2022)
Abstract Background Expanding HIV services by decentralizing provision to primary care raises a possible concern of HIV-related stigma and discrimination (SAD) from health care workers (HCWs) as new service points gain experience in HIV care delivery during early implementation. We surveyed indicators and examined the correlates of HIV-related SAD among HCWs in a decentralizing district of rural Gunungkidul, Indonesia. Methods We conducted a cross-sectional survey on a random stratified sample of 234 HCWs in 14 public health facilities (one district hospital, 13 primary health centers [PHC]) during the second year of decentralization roll-out in the district. We computed the prevalence of SAD indicators and used multivariable logistic regression to identify the correlates of these SAD indicators. Results The prevalence of SAD among HCWs was similarly high between hospital and PHC HCWs for fear of HIV transmission (~71%) and perceived negative image of PHIV (~75%). Hospital HCWs exhibited somewhat lower avoidance of service duties (52.6% vs. 63.7%; p = 0.088) with weak evidence of a difference and significantly higher levels of discriminatory practice (96.1% vs. 85.6%; p = 0.009) than those working in PHCs. Recent interactions with PLHIV and receipt of training lowered the odds of fear of HIV transmission (p <0.021). However, the odds of avoiding care duties increased with receipt of training (p =0.003) and decreased for hospital HCWs (p = 0.030). HIV knowledge lowered the odds of discriminatory practice (p = 0.002), but hospital facility and nurse/midwife cadres were associated with increased odds of discriminatory practices (p <0.021). No significant correlate was found for perceived negative image of PLHIV. Conclusion HIV-related SAD among HCWs can be prevalent during early decentralization, highlighting the need for timely or preparatory interventions with a focus on building the capacity of hospital and non-physician workforce for positive patient-provider interactions when delivering HIV care.